Bending cyclic behavior and scatter-band analysis of aluminum alloys under beneficial and detrimental conditions through high-cycle fatigue regime - Mohammad Azadi; Hanieh Aroo (Fracture and Structural Integrity)
This article presents the bending fatigue behavior and the scatter-band analysis of aluminum alloys under beneficial conditions of nano-clay-particles and heat-treating, compared to detrimental conditions of the mechanical stress and the corrosion. Moreover, the sensitivity analysis was also done on the stress level, the pre-corrosion phenomenon, the addition of nano-particles, and applying the heat treatment on the high-cycle bending fatigue lifetime of the aluminum-silicon alloy. For this objective, gravity and stir-casting processes were done for aluminum alloy and nano-clay-composite specimens and then, standard samples were machined from initial casted cylinders. Furthermore, rotary fatigue tests were performed under cyclic bending loadings, through the high-cycle fatigue regime. Some samples were pre-corroded in the sulfuric acid for 200 hours. Based on the sensitivity analysis on experimental data by the Minitab software, the obtained results indicated that the stress level was the effective parameter on the fatigue lifetime. The meaningful regression model was calculated and calibrated on the logarithmic scale of the fatigue lifetime. Then, the second sensitive parameter was demonstrated as the pre-corrosion, which caused significant degradation of fatigue properties in the material. The last-ranked factor was related to nano-particles for the beneficial effect on the improvement of the high-cycle fatigue lifetime. The scatter-band analysis illustrated that nano-particles and heat-treating changed the scattering behavior of experimental data.